Some reflections on the social and economic organisation of Connemara - O Buachalla, Liam (Statistical and Social Inquiry Society of Ireland, 1937)
To begin with I think some apology is due for this paper. The apology is due, not so much on account of the subject, but because of the manner in which it has been treated. When I took the matter in hand, I experienced a good deal of difficulty, mainly in deciding with which, of the great mass of interesting phenomena relating to the area, I should deal. Another difficulty arose owing to the fact that conditions differ so much from place to place; opinions, even of people living in the same townland, differ so widely, that I found it hard to come to any definite conclusions on many points. I have tried, in such matters as I have selected for the paper, to treat Connemara as a whole, as a unit. Hence, I have had, as a rule, to content myself with averages.
Read on Friday, 29th January, 1937.
Keywords: Connemara; Land use; 314.15